Upaya Meningkatkan Mutu Keterampilan Dasar Mengajar Melalui Simulasi Peer Teaching Berbasis Teknik Nyaya Darsana - Juliantari, Ni Kadek (Jurnal Penjaminan Mutu, 2018)
This study aims to improve the basic skills of teaching sixth semester students of the Hindu Education Study Program STKIP Agama Hindu Amlapura 2016/2017 academic year through the application of peer teaching simulation based on Nyaya Darsana technique. The subjects in this study were the sixth semester students of the Hindu Education Study Program 2016/2017 academic year totaling 31 people. The data in this study were collected by tests and the results were analyzed quantitatively supported by qualitative interpretations. The results show that the application of peer teaching simulation with Nyaya Darsana technique can improve the basic teaching skills of the sixth semester students of the Hindu Education Study Program STKIP Agama Hindu Amlapura 2016/2017 academic year from the percentage of success in the first cycle of 87,10% to 93,55% in cycle II. Meanwhile, the average value also increased from 73.42 in the first cycle to 74,97 in the second cycle. Therefore, the application of peer teaching simulation with Nyaya Darsana technique is recommended to be used in lectures that target the formation of skills or competencies of prospective teachers.